PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIKA DI SMPN 13 PADANG - Lidia Putri Anggraini (Jurnal Edukasi dan Penelitian Matematika, 2018)
The mathematical  communication  skills is one of the capabilities  that must be possessed by each learners. This study aims to determine the effect of mathematical  communication  skills learning using think talk write type learning model with conventional  learning.  This type  of research  is a pseudo  experiment  with the design  of research  static  group design. Data on the mathematical  communication  skills of learners  were taken through the result of communication skills tests and analyzed by using U Mann Whitney test. The result showed that the mathematical communication  skills of learners using the TTW type learning model is better than the conventional  learning mathematical  communication skills of learners using the conventional learning. Keywords — mathematical communication skills, Think Talk Write, conventional learning.